Novel speed test for evaluation of badminton-specific movements - Madsen, C. M.; Karlsen, A.; Nybo, L. (The Journal of Strength and Conditioning Research, 2015)
In this study, we developed a novel badminton-specific speed test (BST). The test was designed to mimic match play. The test starts in the center of the court and consists of 5 maximal actions to sensors located in each of the 4 corners of the court. The 20 actions are performed in randomized order as dictated by computer screen shots displayed 1 second after completion of the previous action. We assessed day-to-day variation in elite players, and specificity of the test was evaluated by comparing 30-m sprint performance and time to complete the BST in 20 elite players, 21 skilled players, and 20 age-matched physical active subjects (non-badminton players). Sprint performance was similar across groups, whereas the elite players were significantly (p = 0.05) faster in the BST (total test time: 32.3 ± 1.1 seconds; average: 1.6 seconds per action) than the skilled (34.1 ± 2.0 seconds) and non-badminton players (35.7 ± 1.7 seconds). Day-to-day coefficient of variation (CV) of the BST was 0.7% for the elite players, whereas CV for repeated tests on the same day was 1.7% for elite, 2.6% for skilled, and 2.5% for non-badminton players. On this basis, we suggest that the BST may be valuable for evaluation of short-term maximal movement speed in badminton players. Thus, the BST seems to be sport specific, as it may discriminate between groups (elite, less trained players, and non-badminton players) with similar sprinting performance, and the low test-retest variation may allow for using the BST to evaluate longitudinal changes, for example, training effects or seasonal variations.